Śrībhāṣyam: viṣayānukramaṇī-adhikaraṇasārāvalī-adhikaraṇaviṣaya-adhikaraṇaviṣayavākyaiḥ sahitaḥ (catuḥsūtrībhāgaḥ) - Ramanuja (Bhāratīya Vidyā Prakāśana, 2018)
Commentary on Bādarāyaṇa's Brahmasūtra, basic work of the Vedanta school in Hindu philosophy; Viśiṣṭādvaita viewpoint